Network security : data and voice communications - Simonds, Fred. (New York : McGraw-Hill, 1996)
Network Security is the first comprehensive hands-on guide to securing data and voice networks from both internal and external security threats.
Starting with the basics, this practical reference quickly brings the reader up to speed on such timely topics as conducting effective security audits; security risks inherent in connecting to the Internet; protecting your network from the latest viruses; incorporating the latest government encryption initiatives and policies; managing passwords, encryption, authentication, and access control; and how to construct "firewalls" to keep hackers out of your system.
Packed with real-life examples, this working reference includes a product selection checklist covering a wide variety of security hardware and software products currently available.
Ch. 1. Where Do Security Threats Come From? -- Ch. 2. Preventing, Detecting, and Dealing with Viruses -- Ch. 3. Security Standards -- Ch. 4. Authentication Methods -- Ch. 5. Encryption Methods -- Ch. 6. Access Control -- Ch. 7. LAN Security -- Ch. 8. Finding Network Operating System and Operating System Weaknesses -- Ch. 9. Sources of Leaks in LANs and WANs -- Ch. 10. Firewalls: TCP/IP and Internet Security -- Ch. 11. Sources of Leaks in Voice Systems -- Ch. 12. How Much Security is Enough? -- Ch. 13. How to Create a Network Security Policy -- Ch. 14. Where to Start.
Includes bibliographical references and index.
Keywords: Computer security; Computer networks -- Security measures